Analisis Kepatuhan Wajib Pajak Atas Hasil Pemeriksaan Pajak Di PT Multi Color Jakarta Indonesia Tahun 2019 - Tedi Setiawan; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Along with advances in information and communication technology, tax audits have turned into an audit system to test taxpayer compliance. This encourages the Directorate General of Taxes to participate in conducting tax audits to test taxpayer compliance. With this background, this study was conducted to examine taxpayer compliance, as well as the obstacles and efforts faced by taxpayers in tax audits. This study uses a qualitativedescriptive approach, with data collection through observation, interviews and documentation. The results of this study indicate that the tax audit at PT Multi Color Jakarta Indonesia went well even though there were several obstacles encountered in the audit process, for example, the required audit files were not ready, the DGT server sometimes still made errors and the audit SOP was not understood. Efforts that must be made by PT Multi Color Jakarta Indonesia are preparing the required inspection files, repairing servers and understanding inspection SOPs.